Effect of Andrographis paniculata a Phytobiotic on Consumption, Feed Conversion and Mojosari Duck Egg Production - Yulianti , Dyah Lestari; Trisunuwati, Pratiwi; Sjofjan, Osfar; Widodo, Eko (International Journal of Poultry Science, 2015)
The aim of this research was to investigate the effect of Andrographis paniculata leaf powder as a phytobiotic on feed consumption, feed conversion and egg production of the Mojosari duck (Mojosari anas plathryncos). One-hundred 24-month-old Mojosari ducks were given basal feed with different concentrations of Andrographis paniculata leaf powder as a feed additive. Experiments were arranged with a completely random design, with five leaf powder concentrations, each replicated four times; A. paniculata leaf powder was added to rations in the following concentrations: 0% (P0), 0.2% (P1), 0.4% (P2), 0.6% (P3) and 0.8% (P4). Data was analyzed using analysis variants and if there was a difference between treatments, those data were further subjected to a least significant difference test; variables included feed consumption, daily egg production and feed conversion. Results showed that A. paniculata leaf powder significantly affected (p0.05) on feed consumption. Average feed consumption per treatment (P0, P1, P2, P3, or P4) was 136.77, 137.82, 135.8, 139.47 and 138.97 g/bird/d, respectively. Average feed conversion values were 9.35 (P0), 5.92 (P1), 4.93 (P2), 7.01 (P3) and 13.50 (P4) and average egg production percentage per treatment was 23.18% for P0, 33.73% for P1, 42.22% for P2, 28.25% for P3 and 14.61% for P4. It was concluded that 0.4% A. paniculata leaf powder was optimal for its phytobiotic actions on Mojosari ducks.